(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Coconut is widely known as the tree of life. Every part of the tree is useful and therefore, coconut palm is an important economic crop of the local people. Neera is the exudate obtained from the unopened inflorescence of coconut palm (Cocos nucifera). It is healthy and therapeutic drink since it is rich in Vitamin C, has more food calories than milk, fights diabetes, cancer, electrolyte deficiency and even hair fall. Neera is rich in minerals and vitamins and it contains glucamic acid necessary for protein synthesis. It aids in digestion health. Neera contains vitamins (A and C), which have anti - oxidant properties thereby preventing damage or death of cells. Neera contains acids nicotinic acid and riboflavin and also can be consumed by people suffering from diabetes since it has a low glycemic index and a low glycemic load. In the study discuss about chemical composition including total sugar, reducing sugar, ethanol and vitamins.